Perbedaan Hasil E-Line Ricketts Menggunakan Digital Vernier Caliper dan Fotogrametri - Azwa Wibowo Putri, Gienzafira; Arief Budiman, Johan (Jurnal Kedokteran Gigi Terpadu, 2025)
Background: The E-line is a line drawn from the Pronasale (Pn) to the Pogonion (Pg). With the development of technology, there are methods that can be used during the measurement process through digital photos, namely photogrammetry. Photogrammetry is defined as an art and science of technology used to extract information through physical objects from the process of capturing, measuring and interpreting photographic images. Objectives: To see the difference in the measurement results of the E-line according to Ricketts using digital vernier caliper and photogrammetry. Methods: 32 people were required as subjects who met the inclusion criteria to take measurements using digital vernier caliper and photogrammetry. Results: The average value of the upper lip distance to the E-line using a digital vernier caliper is 1.80 mm, and the average value of the lower lip is 1.99 mm. As for the average value of the upper lip distance to the E-line with photogrammetric techniques is 1.53 mm, and the average value of the lower lip distance to the E-line is 1.65 mm. The t-independent test results showed no significant difference between the two measurements. (p > 0,05). Conclusion: There is no significant difference between measurements using digital vernier caliper and photogrammetry.